Additive-induced pH determines bacterial community composition and metabolome in traditional mustard seed fermented products - Bora, Sudipta Sankar; Dullah, Samim; Dey, Kuntal Kumar; Hazarika, Dibya Jyoti; Sarmah, Unmona; Sharma, Darshana; Goswami, Gunajit; Singh, Naorem Romen; Barooah, Madhumita (Frontiers in Sustainable Food Systems, 2022)
Kahudi and Kharoli are unique naturally fermented mustard seed products prepared and consumed in the northeastern region of India. The pre-fermentation processing of mustard seeds (soaking, pan-frying, mixing with alkaline or acidic additives, airtight packaging) renders a stringent fermentation environment. The metabolic activities of fermenting bacterial populations yield a myriad of glucosinolate-derived bioactive components which have not been described earlier. This present study employed integrated 16S rRNA amplicon sequencing and LC-MS-based metabolomics to elucidate the bacterial diversity and metabolome of the two fermented mustard seed food products. Univariate and multivariate analyses of metabolomics data revealed differential abundances of a few therapeutically-important metabolites viz., sinapine, indole-3-carbinol, γ-linolenic acid in Kahudi, and metabolites viz., β-sitosterol acetate, 3-butylene glucosinolate, erucic acid in Kharoli. A metagenomic investigation involving the 16S rRNA (V3-V4) amplicon sequencing showed the dominance of Firmicutes (99.1 ± 0.18%) in Kahudi, and Firmicutes (79.6 ± 1.92%) and Proteobacteria (20.37 ± 1.94%) in Kharoli. The most abundant genera were Bacillus (88.7 ± 1.67% in Kahudi; 12.5 ± 1.75% in Kharoli) followed by Lysinibacillus (67.1 ± 2.37% in Kharoli; 10.4 ± 1.74% in Kahudi). Members of both these genera are well known for proteolytic and endospore-forming abilities which could have helped in colonizing and thriving in the stringent fermentation environments.